Linguopoetic presentation of concept MOTHER (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with peculiarities of presentation of concept MOTHER in the poetry. It is emphasized on the search of perceptive images, which is based on feelings. Visual, tactile, olfactory, aural feeling images and their verbalization are analyzed. The meaning filling and associative connections of searched concept are presented and illustrated.
Keywords: concept; feeling image; poetic image; meaning filling; associative connections